Evaluation Of Bioactive From Marine Brown Algae Sargassumilicifolium For Antiulcer Activity Using Isolatedchicken Stomachmodel -An Alternative Approach (Journal of Pharmaceutical Negative Results, 2023)
Sargassumilicifolium, family Phaeophyceae, commonly known as brown algae,the most interesting phyla with respect to pharmacological active compounds. The ethno -medicinal uses of Sargassumspecies have been reported on chronic gastric ulcer, lump, dropsy, painful scrotum, and urination problems. A number of pharmacological activities have been reported for Sargassum sp. viz antitumor, cytotoxic,anthelmintic, anticoagulant, hepatoprotective effects and inhibition of enzymes like DNA polymerase& xanthine oxidase.Based on these ethno-botanical clues, the present study is to evaluate the bioactivity screening of crude sulphated polysaccharide from marine brown algae S.ilicifolium for its antiulcer activity using isolated chick stomach model. Since there is restriction of usage of animals, there is a need for an alternative approach to explain the action of drug. Hence an attempt was made to find and explain the antiulcer activity using isolated gizzard and proventriculus (stomach) from Gallus gallusdomesticus (Chicken) obtained from slaughter house. Antiulcer activity was evaluated by inducing ulcer with 0.1N HCl in isolated gizzard and proventriculus from chick using Omeprazole -400µg/ml as standard and crude sulphated polysaccharide fromSargassumilicifolium (400µg/ml) as test. There was a significant reduction in ulceration of the isolated proventriculus tissue from Gallus gallus which was administered with crude sulphated polysaccharide (SPS) and Omeprazole when compared to control which showed a complete damage of the proventriculus. It has been concluded that on comparsion with standard and control, crude sulphated polysaccharide from Sargassumilicifoliumshowed antiulcer activity at moderate dose.